A note on variation in grain and straw fodder quality traits in 437 cultivars of rice from the varietal groups of aromatic, hybrids, Indica, new planting types and released varieties in the Philippines - Virk, Parminder Singh; Xianglin, L.; Blümmel, Michael (Elsevier, 2019)
Four hundred and thirty-seven different cultivars (59 Aromatics, 53 Hybrids, 172 Indica, 92 New Planting Types and 61 Varieties) were analyzed for grain yield (GY), straw nitrogen (N) content, neutral (NDF) and acid (ADF) detergent fiber, acid detergent lignin (ADL), silica, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) and for relationships between GY and these straw fodder quality traits. Highly significant (P < 0.0001) differences between the groups were observed for all traits with hybrid having the highest GY and also the highest mean straw N, IVOMD and ME. With the exception of NDF and ADL in Aromatics highly significant (P = 0.002 to 0.0001) differences were found for all traits among the cultivars in the different groups. Variations in GY and straw fodder quality traits were greater within cultivar groups than among cultivar types. The variations in straw quality traits between cultivars were of livestock nutritional significance. For example, key straw quality traits such as IVOMD varied between cultivars by at least 6.9% units in New Planting Types and up to 12.0% units in Varieties. Cultivar differences in straw quality can be exploited without detriment to GY since inverse relationships were largely absent. Weak overall inverse associations between GY and straw fodder quality traits, that is inverse relationships between straw N, IVOMD and ME and positive relationship between NDF, AD, ADL and silica and GY, were due to two obvious outliers with very low GY.